2011
DOI: 10.1007/s00421-011-2166-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4-week training period on plasma neuropeptide Y, leptin and ghrelin responses in male rowers

Abstract: The aim was to investigate the effect of high-volume low intensity resistance training protocol combined with endurance training on plasma neuropeptide Y (NPY) concentration in rowers. Additionally, leptin and ghrelin, as markers for body energy balance concentrations, were monitored. 12 highly trained national and international level male rowers participated in this study. The participants were tested three times--after reference week (T1), after 2 weeks of high-volume training (T2) and after a recovery week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This is supported by recent work showing that 2 wk of moderate aerobic exercise training in already fit male rowers further increased the capacity for NPY release in response to a subsequent acute exercise challenge [29]. In addition, exercise has been shown to enhance vagal parasympathetic neurotransmission and thereby suppress proinflammatory pathways-another pathway by which chronic pain might be improved.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This is supported by recent work showing that 2 wk of moderate aerobic exercise training in already fit male rowers further increased the capacity for NPY release in response to a subsequent acute exercise challenge [29]. In addition, exercise has been shown to enhance vagal parasympathetic neurotransmission and thereby suppress proinflammatory pathways-another pathway by which chronic pain might be improved.…”
Section: Discussionsupporting
confidence: 63%
“…Plasma concentrations of NPY were measured without extraction using a direct radioimmunoassay (RIA) kit (Euro-Diagnostica-ALPCO Diagnostics; Salem, New Hampshire). The assay sensitivity is ~12.81 pg/mL and has <0.1 percent crossreactivity with NPY [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , peptide YY, pancreatic polypeptide, and other neuropeptides. The intra-assay coefficient of variation (CV) is 4.7 percent, and the interassay CV is 8.4 percent.…”
Section: Neurohormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY is also released in response to various stress stimuli, such as intense exercise, in the GI tract and plays a role in attenuates the HPA axis [41]. The NPY is a 36-amino acid peptide located throughout the gut-brain axis and is the most prevalent neuropeptide in the brain that plays a role in stress resilience, and inflammatory processes [42].…”
Section: Main Textmentioning
confidence: 99%
“…The NPY is a 36-amino acid peptide located throughout the gut-brain axis and is the most prevalent neuropeptide in the brain that plays a role in stress resilience, and inflammatory processes [42]. Rämson et al [41] studied NPY serum levels in 12 highly trained rowers and found that the post-exercise concentrations of NPY increased significantly. Though few studies have studied serum and hippocampal NPY levels in response to exercise, these results suggest it plays a role in reducing the stress response upon intense exercise [41].…”
Section: Main Textmentioning
confidence: 99%